2003
DOI: 10.1081/jas-120018711
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Asthma in School Children from Ciudad Juarez, Chihuahua

Abstract: Asthma and allergic rhinitis were analyzed in a random sample of school children (n=6174) residing in Ciudad Juarez, Chihuahua, Mexico. The International Study of Asthma and Allergies in Childhood methodology was applied through a standardized questionnaire. The sample was obtained with a bietapic design. Cumulative prevalence of asthma and wheezing was 6.8% (95% CI 6.2, 7.4) and 20% (95% of CI 19.7, 21.8) respectively; the prevalence of rhinitis was 5.0% (95% CI 4.5, 5.6). Family history of asthma odds ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 25 publications
3
23
1
5
Order By: Relevance
“…In approximately 10.0% of the patients there was an association of active asthma, rhinitis, and atopic eczema. These data differ from other authors who observed asthma prevalence 3.4 times higher among patients with rhinitis (3, 10).…”
Section: Discussioncontrasting
confidence: 99%
“…In approximately 10.0% of the patients there was an association of active asthma, rhinitis, and atopic eczema. These data differ from other authors who observed asthma prevalence 3.4 times higher among patients with rhinitis (3, 10).…”
Section: Discussioncontrasting
confidence: 99%
“…Our measure of asthma prevalence in Hispanic/Spanish children was similar to that found in a sister study in neighboring Ciudad Juárez, Mexico[52,53]. Klinnert, et al, reported demographic and environmental differences between acculturated and non-acculturated (as measured by language preference) Hispanics, predominantly of Mexican ancestry, in a clinical cohort at risk for asthma in the Southwestern United States[11].…”
Section: Discussionsupporting
confidence: 70%
“…More than half of the studies used ISAAC criteria for the definition of allergic rhinitis. Finally, 11 studies assessed maternal smoking during pregnancy [44],[45],[47][49],[60],[70],[81],[93],[99],[114].…”
Section: Resultsmentioning
confidence: 99%